Bibliometric analysis of peruvian scientific production in cardiology and cardiovascular medicine - Vargas-Fernández, Rodrigo (2021)
Objective. To determine the characteristics and trend of the articles published on cardiology and cardiovascular medicine in the Peruvian context, and to understand how it has changed over the years. Materials and methods. A bibliometric study of original articles published up to 2020 by Peruvian authors in journals indexed under the category “Cardiac & Cardiovascular Systems” in Web of Science (WOS) was performed. The articles were included according to the selection criteria in the Rayyan web application and the bibliometric analysis was performed using the Bibliometrix package in the R programming language and VOSviewer. Results. A total of 159 published articles were included, and an increase in the number of publications since 2015 was observed. The most cited article was a clinical trial by Fitchett et al. and published in 2016. Miranda JJ was the Peruvian author with the highest number of published articles followed by Hernández AV and Málaga G. The institutional affiliation with the highest number of original articles was Universidad Peruana Cayetano Heredia. Regarding the terms or keywords, it was found that most of the published studies had terms related to epidemiology, while in the most recent articles, the terms were related to outcomes or specific interventions that are used in clinical studies. Conclusions. In the last five years, there has been an increase in the scientific production on cardiology and cardiovascular medicine by authors with Peruvian institutional affiliation, with a greater production from the Universidad Peruana Cayetano Heredia. The journal with the highest number of publications by authors with Peruvian institutional affiliation on cardiology and cardiovascular medicine was Circulation, where two of the most cited articles with Peruvian institutional affiliation were also found.